(untitled) (Journal of the College of Basic Education, 2022)
The results of Zearalenone detection in 16 pourtry feeds samples collected from different locations at Baghdad governarate revealed that all tested samples were contaminated in Zearalenone ,samples E,F and G which collected from Zapharania , S.G. and New Baghdad (1) showed the highest contamination level which recorded (10.558 , 9.145 and 11.5) ng/gm while the samples H ,M and P which collected from S.G.(3) , New Baghdad(2) and New Baghdad(3) showed the lowest contamination level which recorded (3.363 , 2.81 and 1.723) ng/gm . the results also showed that Aspergillus spp. recorded the high percentage of occurancy 100% in (E and C) samples and 88.88% in (K) sample.the percentage of Fusarium spp. occurancy rated from 9.09 to 33.33% , sample (P) recorded the lowest percentage of occurancy 9.09% while sample (A) recorded the highest percentage 33.33% .The results of toxigenic ability of 14 Fusarium spp. isolates showed that 12 isolates were toxigenic while 2 isolates were not toxigenic .Isolate J2 which belong to Fusarium graminearum recorded the highest ability 20.047 ng/ml while the isolates A1, I2 and F1 were the lowest (3.03 ,0.037 and 0.053) ng/ml respectively.